2009
DOI: 10.1002/aic.12072
|View full text |Cite
|
Sign up to set email alerts
|

Integration of on‐the‐fly kinetic reduction with multidimensional CFD

Abstract: A reduction approach for coupling complex kinetics with engine computational fluid dynamics (CFD) code has been developed. An on-the-fly reduction scheme was used to reduce the reaction mechanism dynamically during the reactive flow calculation in order to couple comprehensive chemistry with flow simulations in each computational cell. KIVA-3V code is used as the CFD framework and CHEMKIN is employed to formulate chemistry, hydrodynamics and transport. Mechanism reduction was achieved by applying element flux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…A two-dimensional axial symmetric mesh (Figure 1) with 1052 computational cells at bottom dead center (BDC) is employed in KIVA-3V to simulate HCCI engine combustion. The on-thefly reduction is integrated with KIVA-3V and CHEMKIN code to generate locally accurate reduced mechanism for each computational cell during each time step, 39 and DVODE is applied to numerically solve the resulting ODE system based on each reduced mechanism.…”
Section: ■ Proposed Simulation Frameworkmentioning
confidence: 99%
“…A two-dimensional axial symmetric mesh (Figure 1) with 1052 computational cells at bottom dead center (BDC) is employed in KIVA-3V to simulate HCCI engine combustion. The on-thefly reduction is integrated with KIVA-3V and CHEMKIN code to generate locally accurate reduced mechanism for each computational cell during each time step, 39 and DVODE is applied to numerically solve the resulting ODE system based on each reduced mechanism.…”
Section: ■ Proposed Simulation Frameworkmentioning
confidence: 99%
“…For example, the oxidation of n-heptane contains 560 species and 2539 reactions [21]. Previous studies have demonstrated that even with mechanisms with species less than 50, over 90% of the CPU time was consumed in solving the ODE systems in the reactive flow calculation [22]. A solution to this problem is to reduce the reaction mechanism.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, it is usually impossible to measure the concentrations of all the kinetically significant chemical species . Numerically solving these large systems of differential equations in a reasonable time also remains a challenge, in particular when these models need to be implemented in computational fluid dynamics (CFD) codes .…”
Section: Introductionmentioning
confidence: 99%